Recall of general and medical vocabulary and text structure knowledge: An experimental study of English for Medical Purposes - Esmat Noohi Zarein-Dolab (Journal of Medical Education, 2009)
Background and purpose: A 3-unit course is dedicated to general language in medical universities and the vocabulary and text structure of the courses have usually no relation to medical language. We examine whether teaching general language will be as effective as medical language as assessed through recall of general and medical vocabulary and text structure knowledge. Methods: an experimental study was designed, in that, the third year students who had participated in the 3-unit general language classes in the first year of their General Practitioner (GP) program were selected and sat for a 60 MCQ tests. The 60 MCQ tests consisted of 30 questions of general language, 25 vocabulary and 5 comprehension questions and also 30 questions of medical language, 25 technical and semi-technical vocabulary and 5 comprehension questions. In all, 145 medical students attended the exam which took 40 minutes to accomplish. Results: The results of the study indicated that memory retention was significantly lower in general language than medical language. The technical and semi-technical vocabulary items were significantly better recalled and the medical text was significantly better understood by the participants. Conclusion: A 3-unit course in general language may be a futile effort since the students will not be exposed to the same vocabulary and text structure knowledge in later years of their GP program. It is recommended that the focus of all the university English courses be on the medical language. Key words: Medical Vocabulary, English For Specific Purposes, ESP